2016
DOI: 10.1093/intqhc/mzw108
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a short educational intervention on the use of urinary catheters: a prospective cohort study

Abstract: Objective: To assess the effectiveness of implementation of evidence-based recommendations to reduce catheter-associated urinary tract infections (CAUTIs). Design: Prospective cohort study, conducted in 2010-12, with a before and after design. Setting: A major referral university hospital. Participants: Data were collected before (n = 244) and 1 year after (n = 255) the intervention for patients who received urinary catheters. Intervention: The intervention comprised two elements: (i) aligning doctors' and nur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“… 2 , 5 , 12 However, evidence concerning the influence of a CIC support program on healthcare utilization is sparse. Blondal and colleagues 13 evaluated an educational effort focused on catheter use for nursing personnel on medical-surgical inpatient care units. They reported a reduction in the proportion of hospital inpatient days with a catheter, from 44% to 41% ( P = .006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 5 , 12 However, evidence concerning the influence of a CIC support program on healthcare utilization is sparse. Blondal and colleagues 13 evaluated an educational effort focused on catheter use for nursing personnel on medical-surgical inpatient care units. They reported a reduction in the proportion of hospital inpatient days with a catheter, from 44% to 41% ( P = .006).…”
Section: Introductionmentioning
confidence: 99%
“…They reported a reduction in the proportion of hospital inpatient days with a catheter, from 44% to 41% ( P = .006). 13 However, evidence concerning the influence of posthospital CIC-focused education/support programs on healthcare utilization related to CIC is missing.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary tract infections (UTIs) are among the major health problems that affect millions of people (Foxman, 2010; Blondal et al, 2016). Each year, in the United States UTIs account for nearly seven million clinic visits, one million emergency visits, and 100,000 hospital admissions (Schappert, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A prospective study revealed that implementation of an education plan to increase physician awareness of inappropriate catheterization resulted in statistically signiicant decreases in IUC duration, CAUTI incidence and hospital length of stay [35]. A 2016 study showed that a brief education program provided to both nursing and physicians regarding proper IUC indications resulted in a signiicant decrease in the proportion of inpatient days with IUC in place [36].…”
Section: Remembering the Forgoten Iuc (Quality Improvement)mentioning
confidence: 99%